Dissolved and suspended organic matter dynamics in the Cape Verde Frontal Zone (NW Africa) - Valiente, S.; Fernández-Castro, B.; Campanero, R.; Marrero Díaz, María De Los Ángeles; Rodríguez Santana, Ángel; Gelado Caballero, María Dolores; Nieto-Cid, M.; Delgado-Huertas, A.; Arístegui Ruiz, Javier; Álvarez-Salgado, X. A. (Progress in Oceanography, 2022)
The Cape Verde Frontal Zone (CVFZ) is a highly dynamic region located in the southern boundary of the Canary Current Eastern Boundary Upwelling Ecosystem. Due to the interaction of the Cape Verde Front with the Mauritanian coastal upwelling, the area features large vertical and horizontal export fluxes of organic matter. While the flux, composition and biogeochemical role of sinking organic matter have been thoroughly studied, much less attention has been paid to the dissolved (DOM) and suspended particulate (POM) organic matter fractions. Full-depth profiles of DOM and POM were recorded during an oceanographic cruise in the CVFZ, with four consecutive transects defining a box embracing the giant filament of Cape Blanc and the Cape Verde front. The distributions of DOM and POM and their C:N stoichiometric ratios in the epipelagic layer were strongly influenced by the position of the transects relative to the giant filament and the front. Geographical heterogeneity in POM and DOM distributions and elemental composition was also observed within each of the different water masses of contrasting origin present in the area (North and South Atlantic Central Water, Subpolar Mode Water, Mediterranean Water, Antarctic Intermediate Water, Labrador Sea Water and North East Atlantic Deep Water). These facts suggest that water masses properties are re-shaped by biogeochemical processes occurring within the CVFZ. Nevertheless, our analysis indicates that DOM and POM mineralisation represents only 8.1% of the inorganic carbon and 17.8% of the inorganic nitrogen produced by the local mineralisation of organic matter. Intense lateral export of POM and DOM out of the boundaries of the CVFZ is the likely reason behind these low contributions, which confirm the prominent role of sinking fluxes of organic matter for mineralisation processes in this region. The DOM distribution in the CVFZ interior is apparently affected by the dissolution of fast sinking particles. This work was supported by Spanish National Science Plan research ...